A narrative inquiry approach to understanding senior intensive care nurses' experiences of working with new graduate nurses. Issue 21 (22nd May 2021) - Whittam, Susan; Torning, Nerilee; Patching, Joanna
Abstract: Aims and objectives: To report a qualitative inquiry exploring senior registered nurses' stories of experience working with new graduate nurses in the intensive care unit. Background: While new graduate nurses' perceptions of transitioning into professional practice in the intensive care unit have been examined, few studies have explored the experiences of the senior registered nurses working alongside them. Design: A narrative inquiry methodology informed by Dewey's (1938) theory of experience. Methods: Individual in‐depth, unstructured, interactive interviews were conducted with five senior registered nurses. The inquirer co‐composed individual narrative accounts with each participant. Narrative inquiry's three commonplaces of temporality, sociality and place formed the lens of analysis. Thematic analysis identified two overarching threads that resonated across the narrative accounts. This inquiry adheres to COREQ checklist reporting. Results: The overarching threads 'Reverberations' and 'Caring' depict the experiences of senior registered nurses. 'It's Dangerous', 'Patrolling Like Surf Lifesavers', 'We Carry Them', 'Survival Mode' and 'Enjoyable Moments' are minor threads describing the challenges, while 'I've Been There', 'They Must Ask Questions' and 'Not In My Backyard' reveal their insights. Conclusions: Working with new graduate nurses increased senior registered nurses' patient surveillance and workload, contributing to stress, pressure and feeling overwhelmed. However, senior registered nurses felt an obligation to care for new graduate nurses, who they perceived as still acquiring the skills to autonomously care for critically ill patients. Therefore, senior registered nurses require support themselves. Relevance to clinical practice: Senior registered nurses perceive workplace constraints as impeding their capacity to provide sufficient support and surveillance to new graduate nurses. The gap between new graduate nurses' clinical capacity and patients' needs underpins senior registered nurses' recommendation that new graduate nurses should not be placed in intensive care units unless additional workforce support is provided, safeguarding their development as well as patient safety.